2003
DOI: 10.1038/nature01535
|View full text |Cite|
|
Sign up to set email alerts
|

An expressed pseudogene regulates the messenger-RNA stability of its homologous coding gene

Abstract: A pseudogene is a gene copy that does not produce a functional, full-length protein. The human genome is estimated to contain up to 20,000 pseudogenes. Although much effort has been devoted to understanding the function of pseudogenes, their biological roles remain largely unknown. Here we report the role of an expressed pseudogene-regulation of messenger-RNA stability-in a transgene-insertion mouse mutant exhibiting polycystic kidneys and bone deformity. The transgene was integrated into the vicinity of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
279
4
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(292 citation statements)
references
References 7 publications
4
279
4
5
Order By: Relevance
“…It has also been suggested that the Lamr1 gene family in mammals, with the exception of the functional locus, is comprised entirely of retrotransposons or processed pseudogenes. Most processed retroposons are not expressed and have no functional activity, but several active retroposons or pseudogenes have been identified [29][30][31][32] . We show that the active retroposon may cause the pathological condition of ARVD.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that the Lamr1 gene family in mammals, with the exception of the functional locus, is comprised entirely of retrotransposons or processed pseudogenes. Most processed retroposons are not expressed and have no functional activity, but several active retroposons or pseudogenes have been identified [29][30][31][32] . We show that the active retroposon may cause the pathological condition of ARVD.…”
Section: Discussionmentioning
confidence: 99%
“…The pseudogene was discovered fortuitously while conducting a study which involved inserting a Drosophila gene Sex-Lethal randomly into the mouse genome. 27 This gene insertion was fatal for one line of mice. Surprisingly, the Sex-Lethal gene had been inserted in the middle of a pseudogene, Makorin1p, located on murine chromosome 5.…”
Section: Functional Pseudogenesmentioning
confidence: 99%
“…In Ensembl, blasting the sequence of peroxiredoxin‐6‐like pseudogene against that of the peroxiredoxin‐6 gene (BTA16) confirmed that peroxiredoxin‐6 is the parental gene of peroxiredoxin‐6‐like pseudogene and that the latter is likely to be a processed pseudogene, as the parental gene resides on a different chromosome (Vanin 1985; Hirotsune et al . 2003; Kandouz et al . 2004; Bischof et al .…”
Section: Resultsmentioning
confidence: 99%